The influence of effective microorganisms on physiological characteristics of containerized taurus cedar ( Cedrus libani A. Rich.) seedlings - Ayan, Sezgin; Çalışkan, Ebru; ÖZEL, Halil Barış; Çelik, Esra Nurten Yer; Yılmaz, Ergin; Gülseven, Orhan; Akın, Şeyma Selin (FapUNIFESP (SciELO), 2022)
Background: In this study, the impact of Effective Microorganism (EM) applications on some physiological characteristics of 2+0 aged, containerized Taurus cedar (Cedrus libani A.Rich.) seedlings were investigated. EM-1, EM-A, EM-5, and EM-Gold were used as effective microorganism varieties. EM application was repeated twice at two different times. The first application was carried out in April-May 2017 at the beginning of the vegetation period, and the second application was carried out in June-July, when the growth of seedlings was the most active period, according to a randomized plot design with three replications.Results: Physiological measurements on seedlings were carried out at the end of the second vegetation period. According to the results of the study, it was determined that the EM type, dose and application time factors had a significant effect on physiological characteristics such as Chlorophyll a, Chlorophyll b, Total Chlorophyll, Photosynthesis Rate, Transpiration and Relative Humidity. EM-A had a positive effect on photosynthesis rate and EM-5 had a positive effect on all other measured physiological parameters. High dose of EMs had the most positive effect on relative humidity, while medium dose of EMs had the most positive effect on chlorophyll values, transpiration rate and photosynthesis rate. In addition, it was determined that EM application at the beginning of the vegetation period had an increasing effect on all measured physiological parameter values.Conclusion: According to the results of the study, it was concluded that EMs have a positive effect on the physiological quality characteristics of Taurus cedar seedlings and can contribute to the production of seedlings with higher adaptability in afforestation.
Keywords: Cedrus libani; Effective Microorganism; Effective microorganism; Cedrus Libani; Physiology; seedling quality; Seedling Quality; -; Effective microorganism, Taurus Cedar, seedling quality, physiology.; physiology; Taurus Cedar; 15. Life on land